Simultaneously enhanced strength and strain hardening capacity in FeMnCoCr high-entropy alloy via harmonic structure design. (15th January 2021) - Li, Guodong; Liu, Maowen; Lyu, Shaoyuan; Nakatani, Masashi; Zheng, Ruixiao; Ma, Chaoli; Li, Qiushi; Ameyama, Kei
Abstract: Harmonic structure (HS), consisting of coarse-grained (CG) areas uniformly embedded in three dimensional continuously connected ultrafine-grained (UFG) areas, is considered as an effective microstructural design strategy to achieve enhanced strength and ductility in metallic materials. In the present study, HS designed non-equiatomic FeMnCoCr high-entropy alloy samples with tunable shell fractions (ranging from ~16% to ~70%) were successfully prepared via controlled mechanical milling and subsequent sintering. Microstructure observations suggested that the shell region was composed of fully recrystallized UFGs with a mean grain size below 1 µm. Tensile test revealed that the HS designed samples exhibited simultaneously enhanced strength and strain hardening capability than those of the homogeneous structured counterpart. Particularly, the ultimate tensile strength and uniform elongation of the sample with a shell fraction of ~70% were 1228MPa and 12.4%, respectively, demonstrating superior strength-ductility synergy. The underlying mechanisms responsible for the enhanced mechanical properties were discussed. Graphical abstract: Image, graphical abstract